Evaluation of soft tissue marginal stability achieved after excision with a conventional technique in comparison with laser excision: A pilot study - Pragathi Bhat; Srinath L Thakur; Sudhindra S Kulkarni (Wolters Kluwer Medknow Publications, 2015)
Background: Soft tissue excision around natural teeth is carried out to increase the clinical crown lengths, expose the caries apical to the gingival margins and to correct irregular and un-esthetic soft-tissue contours. Aims: The study was carried out with an aim to evaluate the stability of the soft tissue margins after excision either with a laser or scalpel. Materials and Methods: A total of 20 patients indicated for soft tissue excision for correcting soft tissue discrepancies were selected. The patients with thick gingival biotype were included in the study. They were grouped randomly into excision by laser or scalpel methods. The change in the soft tissue positions from the time of excision to 1-month follow-up were evaluated immediate postoperatively, after 2 weeks and after 1-month postrestoration. Results: The soft tissues remained stable in the laser group at 1-month follow-up, in contrast to the scalpel group and were found to be statistically significant, (Student's t-test) (P < 0.05). Conclusion: The soft tissue margins are more stable and stay at the point they were excised with lasers when compared with scalpel.